STUDY ON THE IMPLEMENTATION AND BENEFITS OF THE EX-BUSINESS LAND REDISTRIBUTION PROGRAM FOR THE COMMUNITY IN RANOTONGKOR VILLAGE AND RANOTONGKOR TIMUR VILLAGE TOMBARIRI TIMUR DISTRICT MINAHASA REGENCY - Priyanta, Ragil; Polii, Bobby; Pakasi, Caroline Betsy Diana (Sam Ratulangi University, 2022)
The purpose of this research was to determine and analyze the implementation of land redistribution activities in Minahasa Regency, as well as to know and examine Access Reform after land redistribution activities and the benefits obtained by land redistribution communities in Minahasa Regency. This research was conducted from October to December 2021 in Ranotongkor & East Ranotongkor Villages, East Tombariri District, Minahasa Regency. The data used are primary data and secondary data. This research uses public policy research methods or public policy research. The results of this study indicate that the implementation of land redistribution has been going well. The Access Reform carried out also shows that 100% of the land redistribution recipients have benefited from the activity. The land redistribution carried out in Minahasa Regency also had an impact on the economy of the community receiving land redistribution where 87.5% of the people who were the object of the study experienced an increase in income ranging from Rp. 200,000 to Rp. 5,000,000 per month.